Clinical outcomes and aortic remodeling after Castor single-branched stent-graft implantation for type B aortic dissections involving left subclavian artery - Yuan, Zihui; Zhang, Lihua; Cai, Fei; Wang, Jian (Frontiers in Cardiovascular Medicine, 2024)
The left subclavian artery (LSA) can be intentionally covered by stentgraft to acquire adequate landing zones for a proximal entry tear close to the LSA during thoracic endovascular aortic repair (TEVAR). Castor single-branched stentgraft is designed to treat type B aortic dissection (TBAD) to retain LSA during TEVAR.This study investigates clinical outcome, aortic remodeling, and abdominal aortic perfusion pattern after TEVAR with the novel Castor device. Methods: From November 2020 to June 2023, 29 patients with TBAD involving LSA were treated with Castor single-branched stent-graft. In-hospital clinical outcome and aortic computed tomography angiography (CTA) data were analyzed. CTA was performed pre-operatively and at follow-up to observe stent morphology, branch patency, endoleak, change in true lumen (TL), false lumen (FL), and transaortic diameters, and abdominal aortic branch perfusion pattern.Results: Technical success rate was 96.6%. One failure was that branch section did not completely enter the LSA and main body migrated distally. No in-hospital mortality, paraplegia and stroke occurred. During follow-up, there were one type Ib endoleak and four distal new entry tears, one recurrent type A dissection arose from new entry tear at the ascending aorta, no stent migration was observed, and branch patency rate was 100%. At the thoracic aorta, TL diameters significantly increased, FL diameters markedly decreased, and FL was partially or completely thrombosed in most of patients at follow-up. At the abdominal aorta, there were 33.3% of TL growth and 66.7% of TL stabilization or shrinkage. The initial TL ratio at iliac bifurcation negatively predicted abdominal TL growth after TEVAR with a cut-off of 21.0%. Of the 102 abdominal aortic branches, 94.1% of branches showed no change on perfusion pattern, 3.9% of branches had an increased TL perfusion, and 2.0% of branches had an increased FL contribution.Castor unibody single-branched stent-graft offers an efficient endovascular treatment for TBAD involving LSA. TEVAR with Castor device effectively induced thoracic FL thrombosis and thoracic TL enlargement, and resulted in abdominal TL growth when the initial TL ratio at iliac bifurcation is less than 21.0%.Castor stent-graft.